Gender Differences in Pay Levels: An Examination of the Compensation of University Presidents - Blevins, Dane P.; Sauerwald, Steve; Hoobler, Jenny M.; Robertson, Christopher J. (Organization Science, 2019)
Our paper studies how gender and organizational status affect a university president’s compensation. Similar to previous findings, we hypothesize that women will receive less pay than men. However, we go beyond a dyadic view of individual differences to examine gender’s impact on compensation, and we explicate the importance of institutional forces in understanding the gender pay gap. In doing so, we rely on organizational status and hypothesize that the gender pay gap will be less pronounced as a university’s status rises. Although we find that the gender pay gap persists within the university president context, we also find that as a university’s status rises, the pay gap declines. Moreover, our findings show that the gender pay gap disappears at higher-status universities. Hence, accounting for where the glass ceiling is broken is an important consideration in understanding the gender pay gap. In sum, by integrating a broader institutional perspective to explain gender differences in pay levels, our paper demonstrates the importance of contextualizing gender to better understand its effects on compensation. The online appendix is available at https://doi.org/10.1287/orsc.2018.1266 .